Mobility Hazard on Indian Roads; A Consequence of Inept Traffic Management - Sandhu, Kiran (Prabandhan: Indian Journal of Management, 2012)
Cities in the developing world within the milieu of globalization are experiencing a phenomenon of chaotic traffic as changing urban growth and consumption patterns have brought about a sharp increase in the number of motor vehicles. As a consequence, the rate of accidents and fatality has also increased substantially. Therefore, mobility on the road poses a constant risk and a premature death threat. Road accidents are a serious risk, a byproduct of massive motorization and a largely inefficient traffic management system. This research paper is an attempt to highlight the road traffic accidents as a critical area of concern and posing a severe mobility hazard. In doing so, the trends and dimensions of road traffic accidents in India are elaborated, and it is stressed that proper road traffic management mechanisms should be in place to mitigate the risk on the road.